DESAIN SISTEM INFORMASI PERSEDIAAN BAHAN BAKU SEBAGAI UPAYA MINIMALISASI BIAYA PERSEDIAAN PADA SISTEM MANUFAKTUR - Lie Liana (Jurnal Ilmiah Dinamika Teknik, 2012)
Design of inventory information systems of raw materials needed to assist in planning the warehouse to accurately the amount of raw material inventory so there is no shortage or surplus raw materials. This means that it can be quickly and precisely calculate the amount of raw material inventory in the warehouse, when to order raw materials to suppliers, and when suppliers send the raw material. This will result in companies no shortage of raw material and never will store excess inventory of raw materials, so that inventory costs can be minimized. Keywords: design of inventory information systems, inventory costs